Joint body, circuit board, semiconductor device, and method for manufacturing joint body

JP7644763B2Active Publication Date: 2025-03-12NITERRA MATERIALS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022540197
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-07-27
Filing Date
2021-07-19
Publication Date
2025-03-12
Estimated Expiration
2041-07-19

Smart Images

  • Figure 0007644763000008
    Figure 0007644763000008
  • Figure 0007644763000009
    Figure 0007644763000009
  • Figure 0007644763000010
    Figure 0007644763000010
Patent Text Reader

Abstract

A joining body according to one embodiment of the present invention is characterized by comprising a ceramic substrate, a copper plate, and a joining layer that is positioned on at least one surface of the ceramic substrate and that joins the ceramic substrate and the copper plate, and moreover is characterized in that: the joining layer contains Cu, Ti, and a first element that is one or two selected from among Sn and In; and the joining layer includes a Ti-rich region, in which the ratio (MTi / ME1) of the mass MTi of the Ti to the mass ME1 of the first element is 0.5 or greater, and a Ti-poor region, in which the ratio (MTi / ME1) is 0.1 or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The embodiments described below relate to a bonded structure, a circuit board, a semiconductor device, and a method for manufacturing the bonded structure. [Background technology]

[0002] A bonded body of a ceramic substrate and a copper plate is used as a circuit board on which a semiconductor element or the like is mounted. International Publication No. 2018 / 021472 (Patent Document 1) discloses a ceramic copper circuit board in which a ceramic substrate and a copper plate are bonded. In Patent Document 1, a brazing material containing Ag, Cu, Ti, etc. is used for the bonding layer. In Patent Document 1, a 1×10 -3 Heat bonding is performed under a pressure of less than 1 Pa. Such a 1×10 -3 A pressure below 1 Pa is called a vacuum. The bonding method using Ti is called the active metal bonding method. Because Ti is an active metal, it is easily nitrified or oxidized. In the active metal bonding method, bonding is performed in a vacuum to prevent Ti from nitriding or oxidizing before bonding. To bond in a vacuum, the inside of the bonding device must be made into a vacuum. Since the temperature is raised after a vacuum is created, only batch processing could be applied to the thermal bonding process. The thermal bonding process includes four steps per batch: evacuation, heating, bonding, and cooling. It took more than 24 hours per batch. For this reason, it could not be said to be suitable for mass production. Meanwhile, International Publication No. 2018 / 199060 (Patent Document 2) discloses a heat bonding process in a continuous furnace. In the example of Patent Document 2, bonding is performed with a furnace length of 3 m and a conveying speed of 10 cm / min. Heat bonding can be completed in about 2 hours, including the holding time during the process. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2018 / 021472 [Patent Document 2] International Publication No. 2018 / 199060 Summary of the Invention [Problem to be solved by the invention]

[0004] In Patent Document 1 and Patent Document 2, the joining brazing material contains 40 wt% or more of Ag. Sn and In are also used in the joining brazing material. Ag is an element that easily diffuses into copper plates. Following the diffusion of Ag, Sn and In also diffuse into the copper plate. When Sn or In diffuses into the copper plate, the melting point of the copper plate decreases. When the melting point of the copper plate decreases, it causes deformation during joining and a decrease in the Temperature Cycling Test (TCT) characteristics. It has been found that controlling the distribution of Ti and Sn or In in the joining layer is effective in preventing the diffusion of Sn or In into the copper plate. The present invention is intended to address such problems, and provides a joint in which the distribution of Ti and Sn or In in the joint layer is controlled. [Means for solving the problem]

[0005] The bonded body according to the embodiment includes a ceramic substrate, a copper plate, and a bonding layer disposed on at least one surface of the ceramic substrate and bonding the ceramic substrate and the copper plate, the bonding layer containing Cu, Ti, and a first element which is one or two selected from Sn and In, and the bonding layer has a mass M of the first element. E1 Mass M of Ti relative to Ti Ratio (M Ti / M E1 ) is 0.5 or more, and the ratio (M Ti / M E1 ) is 0.1 or less. [Brief description of the drawings]

[0006] [Figure 1] FIG. 2 is a diagram showing an example of a bonded body according to the embodiment. [Diagram 2] FIG. 4 is a diagram showing an example of a bonding layer of a bonded structure according to the embodiment. [Diagram 3] FIG. 2 is a diagram showing an example of a circuit board according to an embodiment. [Figure 4] 1 is a diagram showing an example of a semiconductor device according to an embodiment; [Diagram 5] 2 is a DSC curve (500 to 600° C.) of the brazing filler metal of Example 1 during a heating process. [Figure 6] 2 is a DSC curve (700 to 900° C.) of the brazing filler metal of Example 1 during a heating process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] The bonded body according to the embodiment includes a ceramic substrate, a copper plate, and a bonding layer disposed on at least one surface of the ceramic substrate and bonding the ceramic substrate and the copper plate, the bonding layer containing Cu, Ti, and a first element which is one or two selected from Sn and In, and the bonding layer has a mass M of the first element. E1 Mass M of Ti relative to Ti Ratio (M Ti / M E1 ) is 0.5 or more, and the ratio (M Ti / M E1 ) is 0.1 or less. FIG. 1 is a schematic diagram showing an example of a bonded body. In FIG. 1, 1 is a bonded body, 2 is a ceramic substrate, 3 is a copper plate, and 4 is a bonding layer. FIG. 1 shows a bonded body 1 in which copper plates 3 are arranged on both sides of a ceramic substrate 2 via a bonding layer 4. In the example of FIG. 1, the vertical and horizontal sizes of the ceramic substrate 2 and the copper plate 3 are the same. The bonded body according to the embodiment is not limited to this form, and may have a structure in which the copper plate 3 is provided on only one side of the ceramic substrate 2. In addition, the vertical and horizontal sizes of the ceramic substrate 2 and the copper plate 3 may be different from each other.

[0008] Examples of the ceramic substrate 2 include a silicon nitride substrate, an aluminum nitride substrate, an aluminum oxide substrate, and an aluminium substrate. The thickness of the ceramic substrate 2 is preferably 0.1 mm or more and 1 mm or less. If the substrate thickness is less than 0.1 mm, the strength of the ceramic substrate 2 may decrease. If the substrate thickness is greater than 1 mm, the ceramic substrate may become a thermal resistor, which may decrease the heat dissipation of the bonded body. The three-point bending strength of the silicon nitride substrate is preferably 600 MPa or more. The thermal conductivity is preferably 80 W / m·K or more. By increasing the strength of the silicon nitride substrate, the thickness of the substrate can be reduced. For this reason, the three-point bending strength of the silicon nitride substrate is preferably 600 MPa or more, and more preferably 700 MPa or more. The thickness of the silicon nitride substrate can be reduced to 0.40 mm or less, and even 0.30 mm or less. The three-point bending strength of an aluminum nitride substrate is about 300 to 450 MPa. On the other hand, the thermal conductivity of an aluminum nitride substrate is 160 W / m·K or more. Since the strength of an aluminum nitride substrate is low, the substrate thickness is preferably 0.60 mm or more. The three-point bending strength of aluminum oxide substrates is about 300 to 450 MPa, but aluminum oxide substrates are inexpensive. The three-point bending strength of Al2O3 substrates is high at about 550 MPa, but their thermal conductivity is about 30 to 50 W / m K. The ceramic substrate 2 is preferably either a silicon nitride substrate or an aluminum nitride substrate. The silicon nitride substrate and the aluminum nitride substrate are nitride ceramic substrates. The nitride ceramic reacts with an active brazing metal material containing Ti to form titanium nitride. The oxide ceramic reacts with an active brazing metal material containing Ti to form titanium oxide. An oxygen-free copper plate or a copper alloy plate can be used for the copper plate 3. The copper plate 3 is preferably oxygen-free copper. As specified in JIS-H-3100 (ISO1337, etc.), oxygen-free copper has a copper purity of 99.96 wt% or more.

[0009] The bonding layer contains Cu, Ti, and a first element which is one or two selected from Sn and In. Cu (copper) is an element that serves as the base material for the bonding layer. Even if Cu diffuses into the copper plate, it will not deteriorate the copper plate. Ti (titanium) is an element that is effective in reacting with the ceramic substrate to form a strong bond. Sn (tin) or In (indium) is an element that is effective in lowering the melting point of the bonding brazing material that forms the bonding layer. As will be described later, in order to obtain the desired bonding layer, it is effective to increase the heating rate. To do this, it is necessary for the material to contain Sn or In. The bonding layer is characterized by having a Ti-rich region and a Ti-poor region. In the Ti-rich region, the mass M of the first element is E1 Mass M of Ti relative to Ti Ratio (M Ti / M E1 ) is 0.5 or more. In the Ti-poor region, the mass M of the first element E1 Mass M of Ti relative to Ti Ratio (M Ti / M E1 ) is 0.1 or less. The Ti content in the Ti-rich region is higher than the Ti content in the Ti-poor region. Fig. 2 is a schematic diagram showing an example of a bonding layer. In Fig. 2, 2 is a ceramic substrate, 3 is a copper plate, 4 is a bonding layer, 4a is a Ti aggregation layer, 5 is a Ti-rich region, 5a is a Ti intermediate region, 6 is a Ti-poor region, and 7 is a diffusion region. In the bonding layer 4 in Fig. 2, the dotted regions are the Ti-rich region 5 and the Ti intermediate region 5a. The dot density of the Ti-rich region 5 is higher than the dot density of the Ti intermediate region 5a.

[0010] A scanning electron microscope - energy dispersive X-ray spectroscopy (SEM-EDX) is used to analyze the mass ratio of Ti to the first element. An example in which the first element is Sn will be described below. The cross section of the bonded body 1 is taken as the measurement area. The cross section of the bonded body 1 is taken as a cross section parallel to the direction perpendicular to the surface of the ceramic substrate 2. When analyzing the mass ratio of Ti to the first element, the measurement area is limited to the bonding layer 4. In other words, the ceramic substrate 2 and the copper plate 3 are not included in the measurement area. As the SEM, a JEOL JSM-IT100 or a device having equivalent performance is used. As the EDX, a JEOL EX-9440IT4L11 or a device having equivalent performance is used. First, an area analysis is performed by EDX in a measurement area of ​​20 μm × 10 μm. The 20 μm in the measurement area is the length in the direction parallel to the surface of the ceramic substrate 2. The 10 μm in the measurement area is the length in the direction perpendicular to the surface of the ceramic substrate 2. The measurement area is set to 20 μm × 10 μm because this is a range suitable for investigating the distribution of the bonding layer components. If the thickness of the bonding layer 4 is less than 10 μm, the measurement area is set to "10 μm × thickness of the bonding layer 4".

[0011] The Ti-rich region 5 is a region of Ti / M E1 ) is 0.5 or more. Ti-poor region 6 is the region where the mass ratio (M Ti / M E1 ) is in the region of 0.1 or less. In active metal joining methods using Ti, the ceramic substrate 2 is joined by a reaction between the Ti in the brazing material and the ceramic substrate 2. As a result, a Ti agglomeration layer is formed on the surface of the ceramic substrate 2. For example, if the ceramic substrate 2 is a nitride ceramic, the Ti agglomeration layer will be a titanium nitride (TiN) layer. If the ceramic substrate 2 is an oxide ceramic substrate, the Ti agglomeration layer will be a titanium oxide (TiO2) layer. Mass ratio in the Ti-rich region (M Ti / M E1 The upper limit of the mass ratio (M) is not particularly limited, but is preferably 1.2 or less. Ti / M E1 If the mass ratio (M) in the Ti-rich region exceeds 1.2, either the amount of Ti is high or the amount of Sn (or In) is low. In such a case, when the heating rate is increased, the bondability may decrease. Ti / M E1 ) is preferably 0.5 or more and 1.2 or less. The presence of the Ti-rich region 5 can suppress excessive diffusion of Sn (or In) into the copper plate. That is, Ti has a trapping effect that keeps Sn in the bonding layer 4. Mass ratio in Ti-poor region 6 (M Ti / M E1 ) is 0.1 or less. By having both the Ti-rich region 5 and the Ti-poor region 6 in the bonding layer 4, it is possible to achieve both the effect of suppressing the diffusion of Sn into the copper plate and the effect of improving the bondability. 6 Mass ratio in (M Ti / M E1 The lower limit of Ti is zero. Zero Ti means that the amount is below the detection limit. A TiSn alloy is present in a part of the Ti-rich region 5. A TiSn alloy may be present in a part of the Ti-poor region 6. Ti agglomerated layer 4a The main component in is titanium nitride or titanium oxide, as described later. The Ti-rich region and the Ti-poor region are distinguished from the Ti agglomerated layer formed on the surface of the ceramic substrate 2. In addition, in the measurement area, Ti / M E1 ) may be in a range of 0.2 to 0.4. Ti / M E1 The region where the ratio of the Ti content between 0.2 and 0.4 is called the intermediate Ti region. The TiSn alloy in the Ti-rich region 5 and the Ti-poor region 6 may also contain intermetallic compounds. Examples of intermetallic compounds include Sn3Ti5 and Sn5Ti6. It is preferable that 50% or more of the TiSn alloy is Sn3Ti5 or Sn5Ti6. The presence of Sn3Ti5 or Sn5Ti6 indicates that the joining reaction has been carried out properly.

[0012] In the Ti-rich region 5, the mass M of the first element E1 Cu mass M Cu Ratio (M Cu / M E1 ) is preferably 0.05 or more and 0.4 or less. In the Ti-poor region 6, the mass ratio (M Cu / M E1) is preferably 3 or more and 10 or less. The presence of Cu in the Ti-rich region 5 and the Ti-poor region 6 can lower the melting point of the bonding layer 4. Lowering the melting point of the bonding layer 4 can improve the bondability even if the temperature rise time is shortened, as described later. The Ti-rich region 5 and the Ti-poor region 6 may contain intermetallic compounds such as CuSn, CuIn, CuSnTi, and CuInTi. The Ti-rich region is mainly composed of TiSn alloy containing a large amount of Sn with a large atomic number. When the cross section of the bonding layer is observed with a backscattered electron image of an SEM, elements with a large atomic number appear whiter than elements with a small atomic number. Therefore, when the backscattered electron image of an SEM is observed with high contrast, the TiSn alloy appears white. The amount of TiSn alloy in the Ti-rich region is sufficiently greater than the amount of TiSn alloy in the Ti-poor region. In other words, the region that appears white in the bonding layer observed with the backscattered electron image can be regarded as a Ti-rich region. The region that is observed as white at high contrast is preferably present in an area ratio of 10% or more per measurement area of ​​20 μm×10 μm. Also, the area ratio of the Ti-rich region can be obtained by observing the backscattered electron image. Also, the upper limit of the region that appears white is preferably 90% in area ratio. It is necessary that both the Ti-rich region 5 and the Ti-poor region 6 exist in the measurement area of ​​20 μm×10 μm. In addition, the area ratio of the Ti-rich region may be obtained by combining with the above-mentioned SEM-EDX. Note that the contrast of the SEM backscattered electron image is such that elements with larger atomic numbers appear whiter. The mass ratio (M Ti / M E1 ) is between 0.5 and 1.2, it becomes easy to distinguish between Ti-rich and Ti-poor regions by contrast. Also, the contrast of SEM electron reflection images can be changed depending on the device. For this reason, a method that uses white shading is effective. Therefore, the method using electron reflection images can be used as a simplified version of the method using EDX. The area ratio of the Ti-rich region is preferably in the range of 10% to 90%, and more preferably 20% to 60%. In addition to the Ti-rich region, the bonding layer also has a Ti-poor region or a Ti-intermediate region. The area ratio of the Ti-poor region is preferably in the range of 10% to 50%. In addition, in a measurement area of ​​20 μm×10 μm, regions other than the Ti-rich region, the Ti-intermediate region, and the Ti-poor region may exist. For example, when a Cu-Sn-Ti-C brazing material is used, a region in which Sn does not exist may be formed. The region in which Sn does not exist does not fall under any of the Ti-rich region, the Ti-intermediate region, and the Ti-poor region. Therefore, as long as the Ti-rich region, the Ti-intermediate region, and the Ti-poor region satisfy the above-mentioned range, a region in which Sn or In does not exist may exist. When the cross section of the bonding layer is divided into two equal parts, the mass ratio (M Ti / M E1 ) is the mass ratio in the copper plate area (M Ti / M E1 For example, when the cross section of the bonding layer is analyzed, the mass of Sn M Sn Mass M of Ti relative to Ti Ratio (M Ti / M Sn ) is preferably less than 1. When the cross section of the bonding layer is analyzed, the mass M In Mass M of Ti relative to Ti Ratio (M Ti / M In ) is preferably less than 1. Dividing the cross section of the bonding layer into two equal parts vertically means drawing a straight line perpendicular to the ceramic substrate surface from the bonding interface between the ceramic substrate and the bonding layer to the bonding interface between the bonding layer and the copper plate, and drawing a straight line parallel to the ceramic substrate surface from the center of the straight line. The bonding interface between the ceramic substrate 2 and the bonding layer 4 is the bonding interface between the ceramic substrate 2 and the Ti aggregation layer 4a. If the ceramic substrate 2 is a nitride-based ceramic substrate, the Ti aggregation layer is a titanium nitride (TiN) layer. The bonding interface between the bonding layer 4 and the copper plate 3 is the furthest point (the furthest point from the ceramic substrate 2) where the components of the bonding layer are connected and in contact with the copper plate 3. Since the components of the bonding layer 4 contain Ti and the first element, the bonding interface between the bonding layer 4 and the copper plate 3 is determined by the diffusion state of these elements. Note that the titanium nitride, which is the Ti aggregation layer, may contain titanium and nitrogen in an atomic ratio other than 1:1. If the ceramic substrate is an oxide-based ceramic, the Ti aggregation layer will be titanium oxide. The titanium oxide used as the Ti aggregation layer can be of various types, such as TiO2, TiO, and Ti2O3. When using an oxide-based ceramic substrate, the above-mentioned titanium nitride is replaced with titanium oxide to determine the bonding interface. When the cross section of the bonding layer is divided into two equal parts, the mass ratio (M Ti / M E1 ) is the mass ratio in the copper plate area (M Ti / M E1 ), it indicates that the amount of Ti in the copper plate side region of the bonding layer is small or the amount of the first element is large. Ti / M Sn ) is less than 1, it indicates that the amount of Sn is greater than the amount of Ti in the bonding layer. Similarly, when the cross section of the bonding layer was analyzed, the mass ratio (M Ti / M In ) is less than 1, this indicates that the In content is greater than the Ti content in the bonding layer. By controlling the distribution of Ti and the first element, it is possible to suppress the diffusion of the first element into the copper plate. This prevents the melting point of the copper plate from decreasing, and suppresses the deformation of the copper plate during bonding. As a result, it is possible to reduce the warping of the bonded body during bonding.

[0013] The height of the diffusion region where the amount of Sn or In diffused into the copper plate is 1 wt% or more from the interface between the bonding layer and the copper plate is preferably 100 μm or less. The height of the diffusion region corresponds to the distance from the interface between the bonding layer and the copper plate to the boundary between the region in the copper plate where the amount of Sn or In diffused is 1 wt% or more and the region where the amount of Sn or In diffused is less than 1 wt%. More preferably, the height of the diffusion region is 50 μm or less. The melting point of the CuSn alloy decreases as the amount of Sn increases. When Sn diffuses into the copper plate, a CuSn alloy is formed on the copper plate. If the amount of Sn diffused is large, the amount of Sn in the CuSn alloy increases. As a result, if the melting point of the copper plate decreases, the copper plate becomes more likely to warp during the joining process or TCT test. Generally, the melting point of copper is 1085°C. If the amount of Sn in the CuSn alloy is 50wt% or more, the melting point of the CuSn alloy becomes 100 to 300°C. If the amount of Sn diffused into the copper plate is small, there is no effect, but if the amount of Sn diffused increases, there is an effect. For this reason, the height of the diffusion region 7 where the amount of Sn or In diffused into the copper plate 3 is 1wt% or more is preferably 100μm or less, and more preferably 50μm or less. When an oxygen-free copper plate is used as the copper plate, the content of Sn or In in the copper plate can be regarded as the amount of diffusion of Sn or In. A copper alloy plate containing Sn or In may be used as the copper plate. In the copper alloy plate, Sn or In is uniformly dispersed. Therefore, the content of Sn or In on the front side of the copper plate (the so-called front side of the copper plate) and the content on the back side of the copper plate (diffusion region 7) are measured, and the content on the front side is subtracted from the content on the back side to calculate the amount of diffusion. The back side of the copper plate is the surface to be bonded to the ceramic substrate. The front side is the surface opposite to the back side and is not in contact with the bonding layer. Even when a copper alloy plate is used, the diffusion of Sn or In is preferably suppressed because the melting point of the copper alloy plate is lowered by the diffusion of Sn or In. The melting point of the copper alloy plate containing Sn or In is lower than the melting point of the oxygen-free copper plate not containing Sn or In. Therefore, the copper plate is preferably an oxygen-free copper plate.

[0014] The thickness of the copper plate is preferably 0.3 mm or more. If the copper plate 3 is thick, the current carrying capacity and heat dissipation can be improved. Therefore, the thickness of the copper plate 3 is preferably 0.3 mm or more, and more preferably 0.6 mm or more. In the bonded body according to the embodiment, the diffusion region 7 in which Sn or In is diffused into the copper plate can be narrowed, so that distortion can be suppressed even if the copper plate is thick. The upper limit of the thickness of the copper plate 3 is not particularly limited, but is preferably 3 mm or less, and more preferably 2 mm or less. Even if the copper plate is more than 3 mm thick, it can be joined. On the other hand, if the copper plate is too thick, the etching process becomes more difficult. The etching process is performed to give the copper plate a pattern shape. For this reason, the thickness of the copper plate is preferably 0.3 mm or more and 3 mm or less. The bonding layer 4 may contain elements other than Cu, Ti, Sn, and In. The other elements include 20 wt % or less of Ag and 2 wt % or less of carbon. The bonded body as described above is suitable for a circuit board. Also, a semiconductor element may be mounted on the circuit board according to the embodiment to be used as a semiconductor device. Fig. 3 is a schematic diagram showing an example of a circuit board. Fig. 4 is a schematic diagram showing an example of a semiconductor device. In Fig. 3 and Fig. 4, 8 is a copper circuit part, 9 is a heat sink, 10 is a semiconductor element, 11 is a lead frame, 20 is a circuit board, and 30 is a semiconductor device. In the circuit board 20 shown in FIG. 3, the copper plate 3 on the front side of the bonded body 1 is processed into a copper circuit portion 8, and the copper plate 3 on the back side is processed into a heat sink 9. The circuit board 20 is produced by providing a circuit shape to the copper plate 3 of the bonded body 1. In the semiconductor device 30 shown in FIG. 4, a semiconductor element 10 is mounted on the copper circuit portion 8 of the circuit board 20. In the semiconductor device 30, a lead frame 11 or the like may be mounted in addition to the semiconductor element 10 as necessary. In the example shown in FIG. 3, the circuit board 20 has a structure in which two copper circuit portions 8 are provided, but the structure of the circuit board 20 is not limited to this example. The number and size of the copper circuit portions 8 can be changed as necessary. The number of the semiconductor elements 10 and the lead frames 11 can also be changed arbitrarily. In addition, in FIG. 3, the copper plate 3 on the back side is a heat sink 9, but a circuit structure may be provided to each of the copper plates 3 on both sides. If necessary, an inclined shape may be imparted to the side surface of the copper circuit portion 8 and the side surface of the heat sink 9. If necessary, the bonding layer 4 may be provided with protruding portions that protrude from the side surface ends of the copper circuit portion 8 and the side surface ends of the heat sink 9. An etching process is preferably used to impart the circuit structure and the inclined shape to the side surface of the copper plate.

[0015] Next, a method for producing the bonded body according to the embodiment will be described. As long as the bonded body according to the embodiment has the above-mentioned configuration, the method for producing the bonded body is not limited. Here, an example of a method for obtaining the bonded body according to the embodiment with a high yield will be described. First, prepare a ceramic substrate 2. Examples of the ceramic substrate 2 include a silicon nitride substrate, an aluminum nitride substrate, an aluminum oxide substrate, and an aluminium oxide substrate. The aluminium oxide substrate is a substrate made of a mixture of aluminium oxide and zirconium oxide. An oxygen-free copper plate or a copper alloy plate can be used as the copper plate 3. The copper plate is preferably oxygen-free copper. As specified in JIS-H-3100 (ISO1337, etc.), oxygen-free copper is a copper plate with a copper purity of 99.96 wt% or more.

[0016] Next, a brazing filler metal is prepared. The brazing filler metal preferably contains 50% by mass or more of Cu, 4% by mass or more and 30% by mass or less of Ti, 5% by mass or more and 40% by mass or less of one or two selected from Sn and In, 0% by mass or more and 20% by mass or less of Ag, and 0% by mass or more and 2% by mass or less of carbon. The brazing filler metal used is one that can be bonded even when a rapid heating process is performed at a temperature increase rate of 20° C. / min or more. The brazing filler metal preferably has an endothermic peak in the range of 520° C. to 590° C. in a DSC curve obtained in a heating step at a heating rate of 20° C. / min.

[0017] DSC curves are obtained by applying heat to a sample using a differential scanning calorimeter (DSC) and measuring whether endothermic and exothermic reactions occur. When an endothermic or exothermic reaction occurs, a peak appears on the DSC curve. A negative peak is an endothermic reaction, and a positive peak is an exothermic reaction. An endothermic reaction indicates that the sample is melting or decomposing. An exothermic reaction indicates that the constituent elements of the sample are reacting with each other to form or solidify a compound (including alloying). The larger the peak, the greater the heat of reaction. Here, a negative peak is called an endothermic peak, and a positive peak is called an exothermic peak. The apex of the peak is called the peak top. The difference between the maximum and minimum points of the peak is called the peak height. For example, an endothermic peak is in the negative direction, so it goes up, down, and up again. An endothermic peak includes changes from maximum point to minimum point to maximum point. This minimum point (the lowest point) is the peak top. Of the maximum points on the low temperature and high temperature sides of the minimum point, the one with the larger value (the largest peak in the positive direction) is considered to be the maximum point. The peak height is the value obtained by subtracting the minimum point from the maximum point. For example, since the exothermic peak is in the positive direction, it goes down, up, and down again. The exothermic peak includes changes from minimum point to maximum point to minimum point. This maximum point (the point where it has risen the most) is the peak top. Of the minimum points on the low temperature and high temperature sides of the maximum point, the one with the smaller value (the peak with the largest negative value) is considered to be the minimum point. The peak height is the maximum point minus the minimum point. In addition, although the end point of an endothermic peak (a peak in the negative direction) may appear to be an exothermic peak (a peak in the positive direction), it is counted as an exothermic peak here. Also, a baseline may be drawn to determine each peak. The DSC used is a NETZSCH TGA-DSC simultaneous thermal analysis device STA449-F3-Jupiter or a device with equivalent performance. The measurement is performed in an Ar (argon) flow with an appropriate amount of brazing material dropped into an alumina container. The measurement is performed with the lid of the alumina container closed. It is necessary to prevent the brazing material from reacting with the atmosphere by measuring in an Ar atmosphere. The amount dropped (mg) is measured using a balance. The sample should be 15 mg or more in solid content.

[0018] The temperature profile for obtaining the DSC curve consists of the above-mentioned heating step, holding step, and temperature decreasing step. The heating step is a step of raising the temperature from room temperature to 950°C at a heating rate of 20°C / min. The holding step is a step of holding at 950°C for 20 minutes. The temperature decreasing step is a step of lowering the temperature from 950°C to room temperature at a temperature decreasing rate of 20°C / min. The holding step is performed after the heating step, and the temperature decreasing step is performed after the holding step. Hereinafter, the DSC curve of the heating step at a heating rate of 20°C / min may be referred to as the DSC curve of the heating step. The DSC curve of the temperature decreasing step at a temperature decreasing rate of 20°C / min may be referred to as the DSC curve of the temperature decreasing step. In the DSC curve, a difference of 0.02 mW / mg or more in heat flow between the baseline and the apex of the protrusion was counted as a peak.

[0019] Fig. 5 shows a DSC curve (500-600°C) of the brazing filler metal used in Example 1 in the heating process, and Fig. 6 shows a DSC curve (700-900°C) of the brazing filler metal used in Example 1 in the heating process. In Figs. 5 and 6, the horizontal axis is temperature (°C) and the vertical axis is heat flow (mW / mg). In Figs. 5 and 6, heat flow is abbreviated as DSC. The DSC curve of the temperature-raising step at a temperature-raising rate of 20°C / min preferably has an endothermic peak in the range of 520°C to 590°C. Also, the DSC curve of the temperature-raising step preferably has an endothermic peak in the range of 730°C to 800°C. The endothermic peak in the range of 520°C to 590°C in the DSC curve of the temperature-raising step is called the first endothermic peak. Also, when there are two or more endothermic peaks in the range of 520°C to 590°C in the DSC curve of the temperature-raising step, the largest peak is called the first endothermic peak. The largest peak indicates a large peak on the negative side. Also, the endothermic peak in the range of 730°C to 900°C in the DSC curve of the temperature-raising step is called the second endothermic peak. When there are two or more endothermic peaks in the range of 730°C to 900°C in the DSC curve of the temperature-raising step, the largest peak is called the second endothermic peak. The largest peak indicates a large peak on the negative side. FIG. 5 is a diagram showing an example of the first endothermic peak. FIG. 6 is a diagram showing an example of the second endothermic peak. The brazing filler metal not containing Ag preferably has a second endothermic peak in the range of 730° C. to 800° C. as shown in FIG.

[0020] The first endothermic peak indicates the decomposition reaction of TiH2. The decomposed hydrogen has the effect of removing impurity oxygen in the brazing material and activating the metal components. Conventional active metal brazing materials use AgCuSnTi brazing materials containing 40 mass% or more of Ag. In conventional active metal brazing materials, the decomposition reaction of TiH2 occurs at 480 to 500°C. In other words, the first endothermic peak does not exist in the DSC curve of conventional active metal brazing materials. The decomposition reaction of TiH2 shifts to the high temperature side, which can suppress the nitriding of the joining brazing material. When a nitride-based ceramic substrate and a copper plate are joined using an active metal brazing material, a Ti aggregate layer is formed on the surface of the ceramic substrate. The decomposition reaction of TiH2 shifts to the high temperature side, which can suppress the nitriding of Ti in the brazing material before it reacts with the ceramic substrate. This makes it possible to join in a nitrogen atmosphere.

[0021] The second endothermic peak indicates the melting reaction between Cu and the first element. Cu and the first element are elements that are the base material of the brazing filler metal. Therefore, the second endothermic peak indicates that the brazing filler metal melts and generates a liquid phase. In the conventional active metal brazing filler metal, the decomposition reaction of TiH2 occurs at 480 to 500°C. That is, the first endothermic peak does not occur in the conventional active metal brazing filler metal. By using the brazing filler metal that generates the first endothermic peak, the temperature difference between the peak indicating the decomposition reaction of TiH2 and the second endothermic peak indicating the melting reaction of Cu and the first element can be reduced. This makes it possible to maintain the bondability even if the temperature rise rate in the bonding process is increased.

[0022] The DSC curve of the temperature lowering step at a temperature lowering rate of 20°C / min preferably has an exothermic peak. The exothermic peak of the temperature lowering step indicates that the compound (alloy) formation or solidification of the bonding layer occurs. The thermal stress is the largest when the molten brazing material solidifies. This is because, after the bonding interface is formed, the members with different thermal expansion coefficients are restrained from each other, and stress due to the difference in thermal expansion occurs during cooling. For this reason, the DSC curve of the temperature lowering step preferably has an exothermic peak at 850°C or less. The DSC curve may have two or more exothermic peaks. Having two or more exothermic peaks indicates that the compound (alloy) formation or solidification of the bonding layer occurs in a multi-stage process. This improves the stress relaxation effect of the bonded body. In addition, it is preferable that the DSC curve of the temperature lowering step at a temperature lowering rate of 20°C / min has an exothermic peak between 450°C and 550°C. The exothermic peak between 450°C and 550°C in the DSC curve of the temperature lowering step at a temperature lowering rate of 20°C / min is called the first exothermic peak. If there are two or more exothermic peaks in this temperature range, the largest peak is called the first exothermic peak. If the exothermic peak of the temperature lowering step is less than 450°C, the solidification temperature is too low and the reliability of the joint may decrease. On the other hand, if the exothermic peak is higher than 550°C, the thermal stress may increase. In addition, when comparing the temperature of the peak top of the first endothermic peak in the temperature increasing step with the temperature of the first exothermic peak in the temperature decreasing step, it is preferable that the temperature of the peak top of the first exothermic peak is lower. The first endothermic peak is mainly generated by the decomposition reaction of TiH2. On the other hand, the first exothermic peak in the temperature decreasing step is an exothermic reaction generated by solidification of the bonding layer or formation of a Ti compound. By setting the position of the peak top of the first exothermic peak in the temperature decreasing step to a lower temperature than the position of the peak top of the first endothermic peak in the temperature increasing step, it is possible to suppress the occurrence of thermal stress in the temperature decreasing step. Note that the temperature decreasing step does not need to have a first exothermic peak as long as it has an exothermic peak. In addition, the same effect can be obtained by having two or more exothermic peaks in the DSC curve in the temperature decreasing step.

[0023] The above brazing materials are heated at a rate of 20°C / min or more. speed Bonding is possible even at a rate of 20°C / min or more. The bonding atmosphere may be a vacuum or a nitrogen atmosphere. Note that a vacuum is defined as a temperature of 1×10 -3 The atmosphere is an atmosphere with a pressure of 70 Pa or less. The nitrogen atmosphere is an atmosphere with a nitrogen content of 70 vol % or more. Examples of components other than nitrogen include argon gas and air.

[0024] In order to control the DSC curve, it is effective to control the brazing material composition. The brazing material preferably contains 50 mass% or more of Cu, 4 mass% to 30 mass% of Ti, 5 mass% to 40 mass% of one or two selected from Sn and In, 0 mass% to 20 mass% of Ag, and 0 mass% to 2 mass% of carbon. The total of Cu, Ti, and the first element is preferably 80 mass% or more, and more preferably 90 mass% or more and 100 mass% or less. The total of Cu and the first element is preferably 70 mass% or more. By substantially lowering the proportion of Ag, the melting point of the brazing material can be increased. This makes it possible to obtain a brazing material having a desired DSC curve even if the heating rate and the cooling rate are increased.

[0025] The average particle size of Cu powder, which is the raw material for brazing material, is D50 The average particle size D of the TiH2 powder is preferably 12.0 μm or less, more preferably 10.0 μm or less. 50 The average particle size D of the Sn powder or the In powder is preferably 6.0 μm or less, and more preferably 4.0 μm or less. 50 The average particle diameter D of the powder C is preferably 16.0 μm or less, more preferably 14.0 μm or less. 50 The average particle diameter D of the Ag powder is preferably 6.0 μm or less, more preferably 4.0 μm or less. 50 The particle size of the powder is preferably 3.0 μm or less, and more preferably 2.0 μm or less. By controlling the particle size of the powder, the reaction of each powder can be made uniform. Average particle size of Cu powder D 50 is the average particle size D of the Sn or In powder 50 It is preferable that the melting point is smaller than 1. As described above, Cu and the first element are the base material for the brazing material composition. Compared to Cu, Sn and In have lower melting points. By increasing the particle size of Sn or In, the reaction between Sn powder and Cu powder or the reaction between In powder and Cu powder can be made homogenous. This allows joining even if the heating rate or cooling rate is increased. It is also preferable that the difference between the heating rate and the temperature drop rate is 20°C / min or less. In other words, it is preferable to satisfy |heating rate-temperature drop rate|≦20°C / min. When the brazing material layer is heated, a melting reaction and a solidification reaction occur. These reactions occur in the heating process and the temperature drop process. By reducing the difference between the heating rate and the temperature drop rate, the stress caused by the reaction can be homogenized. This makes it possible to suppress defects such as warping. It is also effective in controlling the area ratio of the Ti-rich region, Ti-poor region, and Ti-intermediate region.

[0026] A process for bonding a ceramic substrate and a copper plate using the above-mentioned brazing material is carried out. The brazing material is mixed with an organic substance to prepare a brazing material paste. The brazing material paste is applied to the surface of the ceramic substrate 2 (or the copper plate 3) to form a brazing material paste layer. The copper plate 3 (or the ceramic substrate 2) is placed on the brazing material paste layer. The thermal bonding process is carried out in a vacuum or a nitrogen atmosphere.-3 The nitrogen atmosphere is an atmosphere containing 70 vol% or more of nitrogen. The nitrogen atmosphere preferably contains 70 vol% or more of nitrogen, and more preferably 85 vol% or more and 100 vol% or less. The nitrogen atmosphere may contain argon gas or air in addition to nitrogen. When heat bonding is performed in a nitrogen atmosphere, it can be performed under various conditions such as normal pressure, reduced pressure, and increased pressure.

[0027] In the heating step of the heat bonding process, the heating rate is set to 20°C / min or more. In the conventional active metal bonding method, the heating rate is 5°C / min or less. By using a bonding brazing material having the above-mentioned DSC curve, bonding is possible even if the heating rate is increased. The upper limit of the heating rate is not particularly limited, but it is preferably 100°C / min or less. If it is faster than 100°C / min, the bonding property may be reduced. For this reason, the heating rate is preferably 20°C / min or more and 100°C / min or less, and more preferably 30°C / min or more and 70°C / min or less. The temperature is raised to the bonding temperature by the temperature raising process. The bonding temperature is set to 750°C or higher. The bonding temperature is set to a temperature higher than the peak top temperature of the second endothermic peak. The second endothermic peak is located at 730 to 800°C. By setting the bonding temperature to a temperature higher than the peak top temperature of the second endothermic peak, the melting reaction of the brazing material can be properly caused. For this reason, the bonding temperature is preferably 750°C or higher, and more preferably 800°C or higher. The upper limit of the bonding temperature is preferably 1000°C or lower. If the bonding temperature is higher than 1000°C, it approaches the melting point of copper (1085°C) and the copper plate may be deformed. The bonding temperature is preferably maintained for 10 minutes or more. The time maintained at the bonding temperature is called the heating holding time. The heating holding time is preferably 10 minutes or more and 100 minutes or less. If the heating holding time is less than 10 minutes, there is a possibility that the time for the brazing material to melt and solidify is insufficient. Also, if it is longer than 100 minutes, there is a possibility that Sn or In will diffuse too much into the copper plate.

[0028] After the heating holding time is over, a temperature-lowering process is performed. The temperature-lowering process is a process of cooling from the joining temperature to room temperature. The temperature-lowering rate is set to 20°C / min or more. In conventional active metal joining methods, the temperature-lowering rate was about 5°C / min. By using a joining brazing material having a DSC curve as described above, joining is possible even if the temperature-lowering rate is increased. The upper limit of the temperature-lowering rate is not particularly limited, but it is preferably 100°C / min or less. If it is faster than 100°C / min, there is a possibility that the joining property will decrease. For this reason, the temperature-lowering rate is preferably 20°C / min or more and 100°C / min or less, and more preferably 30°C / min or more and 70°C / min or less. If necessary, the heat bonding step may be performed while a weight is placed on the bonded body 1.

[0029] The bonding process described above allows the bonding body 1 to be produced. By increasing the temperature rise rate in the temperature rise process and the temperature drop rate in the temperature drop process, the amount of heat applied to the bonding body 1 can be reduced. As a result, the distribution of Ti and the first element in the bonding layer can be controlled. In addition, the amount of Sn (or In) diffused into the copper plate can be reduced. Since the amount of heat to the bonded body 1 can be reduced, warping of the bonded body 1 and distortion of the copper plate 3 can also be reduced. The resulting bonded body 1 is etched and processed into a circuit board 20. If necessary, multiple pieces may be obtained. Multiple pieces are obtained by cutting a large bonded body to obtain small bonded bodies. There are also methods for dividing the bonded body or dividing the ceramic copper circuit board. A scribing process may be performed to make it easier to divide. 。

[0030] (Example) (Examples 1 to 5, Comparative Example 1, Reference Examples 1 to 2) The brazing filler metals were prepared as shown in Tables 1 and 2. Table 1 shows the particle size of the raw material powder, and Table 2 shows the composition ratio.

[0031] [Table 1]

[0032] [Table 2]

[0033] The brazing filler metal components according to the examples and comparative examples were mixed with an organic binder to prepare brazing filler metal pastes. The DSC curves of each brazing filler metal paste were measured using a DSC. As the DSC, a NETZSCH TGA-DSC simultaneous thermal analysis device STA449-F3-Jupiter was used. The measurement was performed in an Ar flow by dropping an appropriate amount of brazing material into an alumina container. The measurement was performed with the lid of the alumina container closed. The temperature program was a heating rate of 20°C / min, held at 950°C for 20 minutes, and a cooling rate of 20°C / min. A sample of 15 mg in solid content was used. The presence or absence of the first endothermic peak and the second endothermic peak during the temperature rise process was examined. The peak top temperatures were also examined. The results are shown in Table 3.

[0034] [Table 3]

[0035] As can be seen from the table, the brazing filler metal according to the embodiment had a first endothermic peak and a second endothermic peak. In contrast, the endothermic peak indicating the decomposition reaction of TiH2 was less than 520°C in the comparative example 1. That is, the first endothermic peak was not observed. Next, a silicon nitride substrate was prepared as the ceramic substrate. The silicon nitride substrate had a thermal conductivity of 90 W / m K, a three-point bending strength of 600 MPa, and dimensions of 50 mm length x 40 mm width x 0.32 mm thickness. An oxygen-free copper plate measuring 50 mm length x 40 mm width x 0.5 mm thickness was prepared as the copper plate. 30 μm of brazing paste was applied to both sides of the ceramic substrate, and a copper plate was placed on top of the brazing paste. Next, a thermal bonding process was carried out. The bonding atmosphere was uniformly a nitrogen atmosphere. The bonding conditions were also uniformly 850°C x 20 minutes. The temperature rise rate and temperature fall rate were set to the conditions shown in Table 4.

[0036] [Table 4]

[0037] The bonded bodies were manufactured by the above-mentioned steps. Ten bonded bodies were manufactured for each of the example and the comparative example. Next, the cross-sectional structure of the resulting bonded body was observed. The cross-section of the bonded body was observed by SEM-EDX. A measurement area of ​​20 μm × 10 μm in the bonded layer was observed, and the Ti-rich and Ti-poor regions were observed. The cross-sectional structure was observed at three random locations that did not overlap each other. The presence or absence of Ti-rich and Ti-poor regions was determined as "present" if they were observed in all three locations, and "absent" if they were not observed in even one location. In addition, the lower and upper limits of the measurement results were recorded as the area ratio. In addition, the mass ratio of Cu to Sn was calculated as the average value of the ratio of the mass of Cu to the mass of Sn. The diffusion area of ​​Sn into the copper plate was also observed. Sn Mass M of Ti relative to Ti Ratio (M Ti / M Sn The region where the mass ratio (M Ti / M Sn ) is less than 0.1, the Ti-poor region. When the bonding layer is divided into two parts from the center, the mass ratio (M Ti / M Sn ) is the mass ratio in the copper plate area (M Ti / M Sn In addition, when the cross section of the joint was analyzed, the mass ratio (M Ti / M Sn ) was less than 1. In addition, the positions where Sn was observed in an amount of 1 mass % or more in the copper plate were determined as the Sn diffusion region in the copper plate. The results are shown in Tables 5 and 6.

[0038] [Table 5]

[0039] [Table 6]

[0040] As can be seen from the table, in the joints according to the examples, Ti-rich and Ti-poor regions were observed in the joint layer. Ti / M Sn ) was in the range of 0.5 to 1.2. In addition, one or two intermetallic compounds, Sn3Ti5 and Sn5Ti6, were detected in the Ti-rich and Ti-poor regions. When the bonding layer was observed using SEM backscattered electron images, the areas that appeared white in the high contrast backscattered electron images were roughly consistent with the Ti-rich areas identified from the SEM-EDX analysis results, demonstrating that using SEM backscattered electron images is an effective method for investigating the area ratio of Ti-rich areas. The height of the Sn-diffused region in the copper plate was also small, at less than 100 μm, or even less than 50 μm. It can be seen that a brazing filler metal with a DSC curve that has a specified peak at a heating rate and cooling rate of 20°C / min is effective in suppressing the diffusion of Sn into the copper plate. In contrast, in the comparative example, no Ti-rich region was observed, and the height of the Sn-diffused region in the copper plate exceeded 100 μm. Next, the amount of warping of the resulting bonded body and the bonding strength of the copper plates were measured. The amount of warping was measured on the long side. Products with a warping amount of 0.3 mm or less for all 10 pieces were rated as the best product (◎). Products with a warping amount of more than 0.3 mm for 1 to 3 pieces were rated as good products (◯). m Products with four or more pieces exceeding this limit were deemed defective (x). The bonding strength of the copper plate was defined as peel strength. Specifically, a peel test sample was prepared for each Example and Comparative Example. The sample was a rectangular copper plate bonded to a ceramic substrate. At that time, the copper plate was bonded so that one end of the copper plate protruded from the ceramic substrate. The protruding copper plate was pulled vertically to measure the peel strength. The results are shown in Table 7. Moreover, an example in which the temperature increase rate and temperature decrease rate of Example 1 were 5° C. / min was used as Reference Example 1. An example in which the temperature increase rate and temperature decrease rate of Comparative Example 1 were 5° C. / min was used as Reference Example 2.

[0041] [Table 7]

[0042] As can be seen from the table, the bonded bodies according to the examples were excellent in terms of warpage and bonding strength. In contrast, in Comparative Example 1, the Ag content was high, so that proper bonding was not possible when the heating rate and the temperature drop rate were fast. Furthermore, when the difference between the heating rate and the temperature drop rate exceeded 20°C / min, as in Example 5, the amount of warpage was worsened. For this reason, it is found that the difference between the heating rate and the temperature drop rate is preferably 20°C / min or less. In addition, the warpage of Reference Example 1 was small, but the bonding strength was reduced. It can be seen that the brazing filler metals of the examples are suitable for a fast bonding process with a heating rate of 20°C / min or more. The same is true for Reference Example 2. In a nitrogen atmosphere, nitridation progressed in the brazing filler metal containing a large amount of Ag, and the bonding strength was reduced. From the above, it was found that if the brazing material has a DSC curve with a predetermined peak at a temperature increase rate and a temperature decrease rate of 20° C. / min, excellent bondability can be obtained even if the temperature increase rate and the temperature decrease rate in the bonding process are increased to 20° C. / min or more. Therefore, it is found that the bonded body according to the embodiment has a small amount of warping and is excellent in mass productivity.

[0043] Although several embodiments of the present invention have been illustrated above, these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other forms, and various omissions, substitutions, modifications, etc. can be made without departing from the gist of the invention. Modifications of these embodiments are included in the scope and gist of the invention, and are included in the scope of the invention and its equivalents described in the claims. In addition, the above-mentioned embodiments can be implemented in combination with each other. [Explanation of symbols]

[0044] REFERENCE SIGNS LIST 1...bonded body, 2...ceramic substrate, 3...copper plate, 4...bonding layer, 5...Ti-rich region, 6...Ti-poor region, 7...diffusion region, 8...copper circuit portion, 9...copper heat sink, 10...semiconductor element, 11...lead frame, 20...circuit board, 30...semiconductor device

Claims

1. A ceramic substrate; Copper plate and a bonding layer disposed on at least one surface of the ceramic substrate and bonding the ceramic substrate and the copper plate; The bonding layer contains Cu, Ti, and a first element which is one or two selected from Sn and In, The bonding layer has a mass M of the first element. E1 Mass M of Ti Ti The ratio (M Ti / M E1 ) is 0.5 or more and 1.2 or less, and the ratio (M Ti / M E1 ) is 0.1 or less.

2. In the Ti-rich region, mass M E1 Mass of Cu relative to Cu The ratio (M Cu / M E1 2. The bonded body according to claim 1, wherein the ratio of the surface roughness to the surface roughness is 0.05 or more and 0.4 or less.

3. In the Ti poor region, mass M E1 Mass of Cu relative to Cu The ratio (M Cu / M E1 3. The bonded body according to claim 1, wherein the number of the first and second electrodes is 3 or more and 10 or less.

4. The first element is Sn, When the bonding layer is divided into two equal parts, the upper and lower parts, the ratio (M Ti / M E1 ) is the ratio (M Ti / M E1 4. The bonded body according to claim 1, wherein the thickness of the bonded body is greater than or equal to 1 mm.

5. A ceramic substrate; Copper plate and a bonding layer disposed on at least one surface of the ceramic substrate and bonding the ceramic substrate and the copper plate; The bonding layer contains Cu, Ti, and a first element which is Sn, the bonding layer includes a Ti-rich region in which a ratio (M Ti / M E1 ) of a mass of Ti to a mass M E1 of the first element is 0.5 or more, and a Ti-poor region in which the ratio (M Ti / M E1 ) is 0.1 or less, A bonded body, characterized in that when the bonding layer is divided into two equal parts, top and bottom, the ratio (M Ti / M E1 ) in the region on the ceramic substrate side is larger than the ratio (M Ti / M E1 ) in the region on the copper plate side.

6. The first element is Sn, When the cross section of the bonding layer is analyzed, the ratio (M Ti / M E1 6. The bonded body according to claim 1, wherein the number of lattices is less than 1.

7. the copper plate includes a diffusion region in which the amount of the first element diffused from the interface between the bonding layer and the copper plate is 1 wt % or more; 7. The bonded body according to claim 1, wherein the length of the diffusion region in a direction connecting the ceramic substrate and the copper plate is 100 [mu]m or less.

8. the copper plate includes a diffusion region in which the amount of the first element diffused from the interface between the bonding layer and the copper plate is 1 wt % or more; 8. The bonded body according to claim 1, wherein the length of the diffusion region in a direction connecting the ceramic substrate and the copper plate is 50 [mu]m or less.

9. 9. The joined body according to claim 1, wherein the copper plate has a thickness of 0.3 mm or more.

10. A circuit board comprising the bonded body according to any one of claims 1 to 9.

11. A circuit board according to claim 10; and a semiconductor element mounted on the circuit board.

12. A method for producing the bonded body according to any one of claims 1 to 9, comprising the steps of: a bonding brazing material having an endothermic peak at 520°C or higher and 590°C or lower in a DSC curve during a heating process, when the DSC curve is measured at a heating rate of 20°C / min, wherein the ceramic substrate and the copper plate are bonded to each other using the bonding brazing material.

Citation Information

Patent Citations

  • Ceramic-copper assembly and manufacturing method of the same

    JP2013211546A

  • Joint body of ceramic body with metal body and method for joining ceramic body with metal body

    JP2015030658A

  • Circuit substrate and semiconductor device

    WO2015019602A1

  • Assembly of ceramic member and metallic member, and method for producing same

    WO2015166789A1

  • Substrate for power modules

    WO2017200004A1